Controle de qualidade de polímeros - Braga, Rene (Universidade Federal de São Carlos, 2023)
The quality control of polymers is an important area in the materials industry that aims to ensure the quality of polymeric materials used in various applications. Polymers are macromolecular materials widely used in different sectors, including the automotive, aerospace, and packaging industries, among others. Quality control is carried out through various methods, such as chemical analyses, thermal analyses, mechanical analyses, spectroscopy, and others. These methods allow for the characterization of a given material, the detection of impurities, the determination of physical and chemical properties, the evaluation of stability, and other parameters that affect the quality of polymers. Through proper quality control, it is possible to ensure that polymers comply with the necessary specifications for each application, thereby guaranteeing the safety and effectiveness of the final products. This work aims to demonstrate how polymer quality control is conducted, highlighting the methods used for this purpose and the importance of this process in today's world.
Polymer quality control
Keywords: Controle de qualidade; Polímeros; Análise de materiais; Caracterização de materiais; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA